2006
DOI: 10.1016/j.bbabio.2006.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial potassium channels: From pharmacology to function

Abstract: Mitochondrial potassium channels, such as ATP-regulated or large conductance Ca2+ -activated and voltage gated channels were implicated in cytoprotective phenomenon in different tissues. Basic effects of these channels activity include changes in mitochondrial matrix volume, mitochondrial respiration and membrane potential, and generation of reactive oxygen species. In this paper, we describe the pharmacological properties of mitochondrial potassium channels and their modulation by channel inhibitors and potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 65 publications
0
58
0
Order By: Relevance
“…Similar cytoprotective effects can be replicated by pharmacological agents that act on the mito-KATP channels (Szewczyk and Wojtczak 2002). Among these, the channel opener -diazoxide has a complex action on mitochondrial membrane potential, ROS production and mitochondrial permeability transition pore (Dröse et al 2006;Holmuhamedov et al 2004;Szewczyk et al 2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar cytoprotective effects can be replicated by pharmacological agents that act on the mito-KATP channels (Szewczyk and Wojtczak 2002). Among these, the channel opener -diazoxide has a complex action on mitochondrial membrane potential, ROS production and mitochondrial permeability transition pore (Dröse et al 2006;Holmuhamedov et al 2004;Szewczyk et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…This effect has been mimicked via pharmacological intervention using a mito-KATP channel opener, diazoxide (Debska et al 2002;Kicinska and Szewczyk 2003;O'Rourke 2004). Diazoxide has been applied to suppress cell apoptosis and promote cell survival as the prototype mito-KATP channel opener (Kis et al 2003) or others (Holmuhamedov et al 2004;Dröse et al 2006;Szewczyk et al 2006). Niagara et al (2007) demonstrated that "preconditioning" rat skeletal myoblasts with diazoxide had improved the survival rate of the cells under oxidative stress and in the recipient myocardium.…”
mentioning
confidence: 99%
“…NS-1619, a benzimidazole derivative, promotes opening of high-conductance (300 pS) BK Ca channels in membranes of a wide variety of cell types (34). NS-1619-induced effects on smooth muscle can be blocked by charybdotoxin or paxilline, but not by glibenclamide, which indicates that the action of NS-1619 in plasma membranes is predominantly on the BK Ca channel.…”
Section: Discussionmentioning
confidence: 99%
“…PDE5 inhibitors increase the intracellular level of cyclic GMP (cGMP), which in turn activates [K Ca ] channels in both the plasma membrane and the inner mitochondrial membrane (Ahern et al, 2002;Szewczyk et al, 2006;Wang et al, 2008). The positive effects of avanafil on calcium homeostasis may thus be due to its effects on cellular polarization, which are similar to those of acetazolamide, and/or to its triggering of a slight mitochondrial depolarization, which would directly influence mitochondrial calcium homeostasis ( Figure 7K).…”
Section: Discussionmentioning
confidence: 99%